Effect of @diskominfotikbengkulu Instagram Content Quality on the Fulfilment of Tourism Information Needs in Bengkulu City - Juwita Syahfitri; Azis Fajar Pirdaus; Siska Maharani; M Aldy Insen Puzra Pratama (Social Sciences Journal, 2026)
Abstract This study aims to determine the effect of the quality of information content on the Instagram account of Diskominfotikbengkulu on fulfilling the tourism information needs of the people of Bengkulu City. The research approach used is quantitative with an explanatory method. Samples were taken using the Simple Random Sampling technique (part of Probability Sampling) from 46 respondents. Data were collected through structured questionnaires, observation, and documentation, then analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS 4 software. The analysis stages include evaluation of the measurement model (outer model) which includes convergent validity tests (outer loading > 0.70, AVE > 0.50), discriminant validity tests (HTMT < 0.90), and construct reliability tests (Cronbach's Alpha > 0.70, Composite Reliability > 0.70). Furthermore, testing of the structural model (inner model) was carried out through t-statistics and coefficient of determination (R-Square). The results of the study indicate that the quality of information content has a positive and significant effect on fulfilling tourism information needs, with a path coefficient of 0.950 and a p-value of 0.000 (<0.05). This proves that the alternative hypothesis (H1) is accepted, while the null hypothesis (H0) is rejected. The R-Square value of 0.173 indicates that the quality of information content is able to influence the fulfillment of tourism information needs by 17.3%, while 82.7% is influenced by other factors. The quality of accurate, relevant, and interesting content has been proven to be effective in helping people plan their travels. These results emphasize the importance of creative management of government agencies' digital communication media to improve public information services. Keywords: Content Quality, Instagram, Information Needs, Digital Communication, SmartPLS 4